Management of Severe Traumatic Brain Injury: A Single Institution Experience in a Middle-Income Country - Basha, Ahmed Kamel; Mahmoud, Mohamed Ashraf; Al Ashwal, Mohamed Ismail; Aglan, Osama; ElShawady, Sherif Bahaa; Abdel-Latif, Assem Mounir; Elsayed, Ahmed M.; AbdelGhany, Walid (Frontiers in Surgery, 2021)
Introduction: Severe traumatic brain injury (TBI) is a major public health problem usually resulting in mortality or severe disabling morbidities of the victims. Intracranial pressure (ICP) monitoring is recently recognized as an imperative modality in the management of severe TBI, whereas growing evidence, based on randomized controlled trials (RCTs), suggests that ICP monitoring does not affect the outcome when compared with clinical and radiological data-based management. Also, ICP monitoring carries a considerable risk of intracranial infection that cannot be overlooked. The aim of this study is to assess the different aspects of our current local institutional management of severe TBI using non-invasive ICP monitoring for a potential need to change our management strategy. Methods: We retrospectively reviewed our data of TBI from June 2019 through January 2020. Patients with severe TBI were identified. Their demographics, Glasgow coma score (GCS) at presentation, treatments received, and imaging data were extracted from the charts. Glasgow outcome scale extended (GOS-E) at 6 months was also assessed for the patients. Results: Twenty patients with severe TBI were identified on chart review. Ten patients received only medical treatment measures to lower the ICP, whereas the other 10 patients had additional surgical interventions. In one patient, a ventriculostomy tube was inserted to monitor ICP and to drain cerebrospinal fluid (CSF). This was complicated by ventriculostomy-associated infection (VAI) and the tube was removed. In our cohort, the total mortality rate was 40%. The average GOS-E for the survivor patients managed without ICP monitoring based on the clinical and radiological data was 6.2 at 6 months follow-up. The 6-month overall good outcome, based on GOS-E, was 33.3%. Conclusion: Although recent guidelines advocate for the use of ICP monitoring in the management of severe TBI, they remain underutilized in our practice due to many factors. External ventricular drains were mainly used to drain CSF; however, the higher rates of VAIs in our institution compared with the literature-reported rates are not in favor of the use of ICP monitoring. We recommend doing a comparative study between our current practice using clinical-and radiological-based management and subdural or intraparenchymal bolts. More structured RCTs are needed to validate these findings in our setting.